Utility of a repeat PET/CT scan in HPV-associated Oropharyngeal Cancer following incomplete nodal response from (chemo)radiotherapy. (January 2019) - Liu, Howard Yu-hao; Milne, Robin; Lock, Gregory; Panizza, Benedict James; Bernard, Anne; Foote, Matthew; McGrath, Margaret; Brown, Elizabeth; Gandhi, Mitesh; Porceddu, Sandro Virgilio
Highlights: Large cohort of p16-positive oropharyngeal cancer treated with (chemo)radiotherapy. Incomplete nodal response on 12 week PET/CT can be surveilled with repeat PET/CT. 71% of patients convert to complete nodal response on repeat PET/CT at 16 weeks. No detriment to regional control if neck dissection performed after 16-week PET/CT. Negative predictive values remain high for 12- and 16-week PET/CT. Abstract: Objectives: To assess the utility of a repeat positron emission tomography/computed tomography (PET/CT) instead of immediate neck dissection (ND) for incomplete nodal response (IR) in Human Papillomavirus (HPV)-associated oropharyngeal squamous cell carcinoma (OPC) following chemoradiotherapy/radiotherapy [(chemo)RT]. Materials and methods: Patients with non-distant metastatic, node positive (N+) disease treated between Jan/2005 to Jan/2016, achieved complete response at the primary with no distant relapse on a 12-week re-staging PET/CT were evaluated. Patients underwent surveillance after complete nodal response (CR). Patients with IR underwent repeat PET/CT at 16 weeks to direct neck management. Primary endpoints were CR conversion rate and subsequent regional failure following a 16-week PET/CT directed ND. Secondary endpoints were predictive values (PV) of the 12- and 16-week PET/CT for residual nodal disease, predictors for requiring the 16-week PET/CT, 5 year regional, locoregional failure free survival (FFS) and overall survival (OS). Results: 235 patients were evaluated. Median follow up was 56 (range 19–60) months. 41 patients underwent 16-week re-staging PET/CT, 29 (71%) converted to CR. No subsequent regional failures occurred following a 16-week PET/CT directed ND. Positive and negative PV of the 12- and 16-week PET/CT for residual nodal disease was 12% & 98%, and 33% & 97%, respectively. N-category (AJCC/UICC 7th edition) predicted for requiring a 16-week PET/CT on univariate analysis (P-value 0.02). 5 year regional, locoregional FFS and OS was 95.8%, 93.4% and 90.8%, respectively. Conclusion: For N+ HPV-associated OPC achieving IR on the 12-week re-staging PET/CT following (chemo)RT, a repeat 16-week PET/CT can spare patients from unnecessary surgery.